Pre-capitalist reproduction on the Nepal Tarai: semi-feudal agriculture in an era of globalisation - Sugden, Fraser (Informa UK Limited, 2013)
This article highlights the continued significance of pre-capitalist formations in shaping the trajectory of economic transition in peripheral regions, even in an era of neo-liberal globalisation. There is a tendency for Marxist scholars to assume the inevitable “dominance” of capitalism over older modes of production. Using a case study from Nepal's far eastern Tarai, this paper seeks to understand the reproduction of feudal social relations in a region which is both accessible and integrated into regional and global markets. The paper traces the early subordination of indigenous groups to feudalism from the eighteenth century onwards, and the political and ideological processes through which these social relations were reinforced. Through examining the historical role of feudal-colonial alliances, however, the paper notes that pre-capitalist reproduction in Nepal is a dynamic process, actively negotiated and reinforced by the external imperatives of capitalist expansion itself as well as through the entrenched political power of landed classes. Today feudal and capitalist formations co-exist and articulate, with surplus divided between landlords and non-farm employers. Understanding the complex dynamics of feudal or “semi-feudal” reproduction in an era of globalisation is crucial if one is to identify avenues for collective mobilisation against inequitable pre-capitalist and capitalist class relations.